To be a teacher in music social project: musicbiographic narratives (Orfeu, 2022)
This work is an excerpt from a completed Master’s research of Programa de Pós-Graduação em Música da Universidade de Brasília (PPGMUS-UnB), whose objective was to understand what it is to be a music teacher, in the midst of social projects. The work dialogues with researchers in the field of Music Education in social projects, focusing on the quality of teacher training/constitution. The theoretical framework is based on concepts inherent to the teaching of music and its implications for learning, in a more transformative than reproductive perspective, such as Biographization in contemporary times and with reflections on processes of constitution of the subject and the concepts of Place. The research is inscribed in the theoretical-methodological (Auto)Biographic perspective, whose source was an interview of this nature, with the music teacher Valdécio Fonseca, creator of the social project “Music and citizenship”, held in Varjão (DF). The interpretative analysis prioritizes the subjectivity of the subject, the observation of the reflexivity processes of acting and narrating about himself of the research collaborator. By listening carefully to the word given by the teacher, which here appears as another-Author, teacher Valdécio brought out, in his narrative speeches, postures, choices, decision-making and his evaluation of events chosen and narrated by him. The conclusions indicate an epistemology of the biographical subject, which links, in the narratives of the experience, the reasons and emotions capable of leading a social project music teacher to do what he did. In (auto) biographical research in Music Education, the teacher does not tell how he does it, but what he did with his life.
Keywords: music teacher’s life story; social project; interview; (auto)biographical narrative